Determination of maximum loading capacity of polyamidoamine (PAMAM) dendrimers and evaluation of Cu55 dendrimer‐encapsulated nanoparticles for catalytic activity. Issue 10 (6th July 2018) - Patala, Rapelang; Noh, Ji‐Hyang; Meijboom, Reinout
Abstract: Spectrophotometric titrations provide information about the interior of the polyamidoamine (PAMAM) dendrimers, and therefore how nanoparticles are encapsulated. In this work, binding studies were performed to determine maximum loading capacities ( N ) of hydroxyl terminated G4, G5, and G6 PAMAM dendrimers with Cu 2+ ions. The values of N found via spectrophotometric titrations were 16.22, 31.86, and 57.36 for G4‐OH, G5‐OH, and G6‐OH, respectively. The determination of loading capacity was also done using Viva spin filtration, and the results were found to be in agreement with those found via spectrophotometric titrations. From the binding isotherm, the values of equilibrium constant ( K ′) were determined and found to be 0.0488 (G4‐OH), 0.0291 (G5‐OH), and 0.0158 (G6‐OH). Owing to instability of G4‐OH (Cu16 ), G5‐OH (Cu32 ), and G6‐OH (Cu57 ) dendrimer‐encapsulated nanoparticles (DENs) synthesized, G6‐OH (Cu55 ) DENs of average size 2.6 ± 0.3 nm were prepared and were found to be relatively stable. Thus G6‐OH (Cu55 ) catalyst was evaluated for the reduction of 4‐nitrophenol and was found to be catalytically active toward reduction of 4‐nitrophenol. Reaction kinetics of 4NP reduction was thoroughly studied in light of the Langmuir‐Hinshelwood kinetic model, and surface rate k, and the adsorption rates K 4NP, and K BH4 were determined. The reaction was performed at different temperatures, which further expanded the study into determination of thermodynamic (Δ H ‡, Δ S ‡, Δ G ‡, and EA ) parameters.